The milk index, blood biochemistry status and growth performance of local malaysian cow (Bos sundoicus) FED Arthrospira platensis supplement - Shamsudin, Lokman; Ab Rashid, Syarifah; Abdullah, Azman Nirmal; Mohamed, Wan Zahari; Lokman, Hafis Harres (2018)
An experimental feed trial was carried out for 40 days to assess and investigate the bio-physiological effect of locally isolated indigenous Arthrospira platensis on the growth performance, milk quality index of the local female Kelantan cattle bred type trait (Bos sundoicus). Sixteen healthy local Kelantan cows (68.6±8.12 kg, 1.21±0.26 years old) were randomly allotted into four groups, viz. one group fed standard diet and three groups with formulated diets with variable strength of A. platensis supplement. There were significant body weight increments and milk volume as shown by the treated cows (p<0.05) when fed with 2-6g/10kg body weight/d; the milk quality and nutrient composition have demonstrated notable changes. The milk volume of cows treated with A. platensis increased by more than 15% and the milk protein recorded was higher by more than 9% on day 15 when supplemented with Spirulina. However, the sugar content in the treated cows decreased by 13%. Meanwhile, supplementation in cows had elevated the high density lipoprotein (HDL) levels by 12 – 19% (p<0.05) and lowered the total cholesterol (TC) by 12 – 18% on day 30. The liver-kidney markers and related biochemical enzyme indicators in the treated and untreated cows, such as blood urine nitrogen (BUN), creatinine (Cr), urea, uric acid and alanine aminotransferase (ALT) remained stable all the way throughout the experimental period. The aspartate aminotransferase (AST) levels in the treated cows reduced significantly. However, these levels were still within the normal acceptant range of the cattle during the study period.